Power dalam Kekerasan Seksual : (Kajian Teori Michel Foucoult dan Johan Galtung) - Harjoni Harjoni (Saree : Research in Gender Studies, 2021)
Sexual violence has become a major issue in society after several cases of harassment often occur. The purpose of this study, first, is to find out the relationship between sexual violence in the theory of Michel Foucault and Johan Galtung. This study uses a qualitative method which is analyzed with a descriptive approach. The results show that Foucault describes this power relation in terms of Disciplinary Power which can be seen from the existing phenomenon that disciplines the internalization of the subjugation of lower castes into something that is considered normal, while in Galtung's view, the power relations between men and women have a tendency to maintain the status quo of men by oppressing women. Unfortunately, these actions are legitimized by elements of groups and institutions by normalizing these actions.